Optimal Relay Placement in Magnetic Induction-Based Internet of Underwater Things - Khalil, Ruhul Amin; Saeed, Nasir (IEEE sensors journal, 2021)
The advances in developing the Internet of Underwater Things (IoUT) can lead to numerous applications, namely, environmental monitoring, underwater navigation, and surveillance. Magnetic Induction (MI) is a promising communication solution for IoUT networks. In this article, we focus on a deep-ocean monitoring network, where the underwater relays communicate using MI induction. Placement of the relays in such a system is an exciting and challenging task. Therefore, we propose an optimal relay placement solution for relays in MI-based IoUT networks to improve network throughput. First, we formulate the relay placement problem as a non-convex optimization problem. Then, we propose a global optimization technique based on Reverse Convex Programming (RCP) to solve the non-convex function. Finally, we compare the results of the proposed scheme with the uniform deployment to show its effectiveness.